Evapotranspiração, coeficiente de cultura e produção do melão Gália irrigado com água de diferentes salinidades - Melo, Talyana Kadja de (2009)
Irrigation becomes a very important practice when it refers to the Northeast Region, due to the irregular rain cycles, making it the main rational alternative of exploitation of agricultural cultures, mainly in the do Pólo Agrícola Mossoró-Açu/RN area, where the larger demand for water has obliged farmers to use water with higher salinity, being its use conditioned to the tolerance of cultures to the salinity and the handling of irrigation. Moreover, in a project as well as in the handling of irrigation, the evapotranspiration of the culture (ETc) is the most important variability, being it possible to be measured directly by means of lysimeters. However, in the absence of measure equipments of evapotranspiration of the culture, the producers, many times, make use of estimate based on evapotranspiration of reference (ETo) and on the coefficient of the culture (Kc). Given to the exposed above, the present work had as aim to determinate the evapotranspiration and the coefficient of the culture, using irrigation water from different salinities, as well as verifying its effects on the production of the culture. To this end, an experiment was conducted on Fazenda Experimental Rafael Fernandes (Rafael Fernandes Experimental farm), belonging to Universidade Federal Rural do Semi-Árido, in the district of Alagoinha, situated 20 km far from Mossoró-RN, with the Gália melon culture, in an area of de 0.24 ha. The levels of salinity of the water for irrigation were of S1=0.65, S2=1.65, S3=2.83, S4=3.06 e S5=4.73 dS m-1. The experiment consisted of four random blocks, each one divided in the five levels of salinity and three of nitrogen subdivided in each salinity portion (N1: 46,7, N2: 93,4 and N3: 140 kg ha-1). To the ETo estimate a Penman- Monteith equation was used parameterized by the FAO. The weather data necessary for the ETo estimate were collected by an automatic agrometereological station, installed in the experimental area. The ETc was measured by four weighing lysimeters, with an área of 2.25 m2, which were installed in the blocks 1 and 2, in the levels of salinity S1 and S5. The results showed that the ETc decreased between the irrigation water S1 and S5 where the total evapotranspiration during the cycle was of 204.5 and 172.4 mm, respectively. As for the Kc s the medium values were verified in the phenological stages I, II, III and IV, of 0.08, 0.44, 1.06 and 0.88 for the S1 treatment and 0.07, 0.54, 0.75 and 0.60 for the S5, showing that the Kc s obtained for the level S1 were always larger than the Kc s obtained for the level S5, except stage II. As for the production of the culture, effect of water salinity was verified in all the evaluated production components. The commercial and total production had reductions of 4.07 and 3.16 Mg ha 1, respectively, by adding of 1 dS m-1 of salinity in the water of the irrigation.